Idioms in Cognitive Linguistics: Is It All about Conceptual Metaphor Theory? - Kovaliuk, Yurii (B.A.S. British and American Studies, 2022)
The present paper is a study of idioms in cognitive linguistics in an attempt to account for the prevailing trends and prospective directions of research in the field. First, I look at idiomatic expressions from the standpoint of Conceptual Metaphor Theory, with a special emphasis on socio-cognitive and pragmatic aspects of idiom use and comprehension. For this purpose, idioms used in an American legal drama series Suits are analysed. I then proceed with the discussion of the motivational aspect of idioms. In the final analysis, the perspectives for future research of idioms within cognitive linguistic framework are outlined.
Keywords: cognitive linguistics, Conceptual Metaphor Theory, idiom comprehension, idiom motivation, idioms